2017
DOI: 10.21815/jde.017.032
|View full text |Cite
|
Sign up to set email alerts
|

Preparing the Future Dental Hygiene Workforce: Knowledge, Skills, and Reform

Abstract: With the health care delivery system in transition, the way in which oral health care services are delivered in 2040 will inevitably change. To achieve the aims of reduced cost, improved access, and higher quality and to advance population wellness, oral health care will likely become a more integrated part of medical care. An integrated primary care system would better meet the needs of an increasingly diverse and aging U.S. population with uneven access to health care services. By 2040, trends suggest that a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 19 publications
0
30
0
Order By: Relevance
“…For treatment of a higher number of patients including their felt needs and preventive measures, it is important to substantially expand the capacity of general dental practices with the effective use of dental auxiliaries as suggested by literature. [19] According to Fried et al [20] by 2040, many will practice with multidisciplinary healthcare teams in large-group medical and dental practices and in a variety of nontraditional community settings. Gurenlian et al [21] suggested that the integration of dental hygienists into dental healthcare delivery system needs curriculum change, and it should be redirected and strengthened further.…”
Section: Discussionmentioning
confidence: 99%
“…For treatment of a higher number of patients including their felt needs and preventive measures, it is important to substantially expand the capacity of general dental practices with the effective use of dental auxiliaries as suggested by literature. [19] According to Fried et al [20] by 2040, many will practice with multidisciplinary healthcare teams in large-group medical and dental practices and in a variety of nontraditional community settings. Gurenlian et al [21] suggested that the integration of dental hygienists into dental healthcare delivery system needs curriculum change, and it should be redirected and strengthened further.…”
Section: Discussionmentioning
confidence: 99%
“…The adult population over the age of 65 is expected to rise from 15% in 2014 to 24% by 2060 with more adults residing in long-term care facilities. 5 The concept of midlevel dental practitioners is here to stay.…”
Section: President's Messagementioning
confidence: 99%
“…Nevertheless, since nearly 40% of dentists report not being as busy as desired 11 and with the number of dental school graduates expected to reach levels never before seen in the next few years, 23 the backlog of need could be handled fairly rapidly. 26 Eighth, some primary care medical practices are providing basic screening and preventive dental services to low-income children. Further, if by 2040 most publicly financed dental insurance plans were managed by large capitated group practices (as in Oregon), the cost per patient could be much lower than in current fee-for-service plans.…”
Section: Current Supply Of Dentists and Population Demandmentioning
confidence: 99%
“…As more carious teeth are managed chemically rather than surgically, and even fewer initial restorations need to be replaced either by dentists or dental therapists, dental hygienists would have a greater role in caring for these patients and further increasing the number of patients managed per dentist per year. 26 Eighth, some primary care medical practices are providing basic screening and preventive dental services to low-income children. 27 In a few states, some medical practices are employing dental hygienists.…”
Section: Current Supply Of Dentists and Population Demandmentioning
confidence: 99%